PROSES PRODUKSI KERUPUK NASI SEBAGAI SALAH SATU INOVASI CAMILAN SEHAT DAN BERNUTRISI DI DESA KORAJIM - Nia Wati; Haidir Lubis (Bajang Institute, 2023)
The purpose of this research is to create employment and to advance people's lives and improve the local economy. A rice cracker business was established in Korajim Village, Dolok Merawan District, Serdang Bedagai Regency. This location was chosen because it is a strategic location in the village of Korajim, which is a place with a lot of people and also a crossing road for residents. In establishing a rice cracker business, researchers used a SWOT analysis. The promotion methods used are personal selling and internet marketing. The results of this study, namely the rice cracker business can achieve a profit of up to IDR 7,800,000/month assuming all rice cracker products produced (50 pcs/day) are sold out.